Influence of headaches on nurse intentions to leave the profession and the hospital: a cross-sectional survey. Issue 2 (3rd March 2020) - Chang, Hao-Yuan; Shyu, Yea-Ing Lotus; Wong, May-Kuen; Friesner, Daniel; Chu, Tsung-Lan; Teng, Ching-I
Abstract : Background: Few studies had examined whether headaches impact emotional exhaustion among nurses, and nurses' intentions to leave the hospital (current employer) or nursing profession. Objectives/Aims/Hypotheses: To examine the impact of headaches on nurses' self-efficacy and emotional exhaustion, and nurses' intentions to leave the hospital or the profession. Design: A cross-sectional survey design with proportional random sampling was used to collect data. Methods: This study was conducted in one medical center in Taiwan during February and March 2017. Inclusion criteria were full-time registered nurses. Totally, 570 full-time registered nurses were surveyed. Results: Nurse headaches were positively related to emotional exhaustion, which was positively related to the intention to leave the hospital, further positively related to the intention to leave the profession. Self-efficacy was negatively related to the intention to leave the profession. Impact statement and Conclusions: Our findings advise nurse managers to take actions to reduce nurses' headaches.